The description of Stephanostomum spp. (Trematoda: Acanthocolpidae) from fishes of Tonkin bay - Ha, Nguyen Van; Ngo, Ha Duy (Academia Journal of Biology, 2012)
Three species of Stephnostomum Looss, 1899 are described from Tonkin bay, Vietnam. S. ditrematis (Yamaguti, 1939), from the intestine of Seriola dumerili (Perciformes: Carangidae), has 36 circum-oral spine; ventral spines slightly shorter than dorsal; oral spines shorter than aboral. S. bicoronatum (Stossich, 1883), from the intestine of Johnius carouna (Perciformes: Sciaenidae), has 30 circum-oral spine with ventral hiatus; aboral spines smaller than oral in mid-ventral area; seminal vesicle undivided; pars prostatica tubular, relatively short; ejaculatory duct long; testes near posterior end of hindbody. Stephnostomum sp., from the intestine of Harpadon nehereus (Aulopiformes: Synodontidae), has 28 circum-oral spine; prepharynx long (25% of body length). Stephnostomum sp. is morphometrically closer to S. fistulariae (Yamaguti, 1940).